Experimental Study on Preparation and Performance of Concrete With Large Content of Fly Ash - Li, Changyong; Geng, Haibin; Zhou, Siyi; Dai, Manman; Sun, Baoshan; Li, Fenglan (Frontiers in Materials, 2022)
Producing concrete with large content of fly ash attracts increasing attention in low carbon building materials. In this paper, the fly-ash concrete (FAC) with a content of fly ash no less than 50% total weight of binders was developed. The adaptability of fly ash used for concrete was firstly examined by testing the water requirement of normal consistency and the setting time for cement fly-ash paste, and the strengths of cement fly-ash mortar at the curing age of 7 and 28 days. The factors of water-to-binder ratio from 0.3 to 0.5, the content of fly-ash from 40% to 80%, and the excitation measures with additional Ca(OH)2 and steam curing at initial were considered. After that, the FAC was designed by adding an excessive content of fly ash to reduce the water-to-binder ratio from 0.50 to 0.26, and the content of fly-ash varied from 52% to 60%. Results show that the cement fly-ash paste presented a reduction of water requirement and an elongation of setting time with the increased content of fly ash. This provides a foundation of maintaining the workability of fresh FAC with a decreased water-to-binder ratio by adding the excessive content of fly ash. The cement fly-ash mortar had a lower early strength due to the slow reaction of fly-ash with Ca(OH)2, which could be improved by steam curing at the initial 24 h due to the excitation of fly-ash activity. At curing age of 28 days, the FAC had the expected axial compressive strength and modulus of elasticity, but the tensile strength was lower than predicted. At the curing age of 56 days, all the basic mechanical properties of FAC reached the prediction. The resistances of FAC to chloride ion penetration and carbonization were realized at a very high level as specified in codes.